Role of Natural Resources and Eco-Innovations in Determination of the Environmental Quality of Pakistan: Evidence through Vector Autoregressive (VAR) Estimation - Hanif, Sobia; Nawaz, Muhammad Atif; Fazal, Snober; Ibraheem, Ruqayya (iRASD Journal of Economics, 2022)
The present study estimates the impact of natural resources, eco-innovations and economic growth on CO2 emissions in Pakistan over 1990-2019 period. For empirical estimation, Vector Autoregressive Model (VAR) and Granger Causality Analysis, Variance Decomposition Analysis and Impulse Response Function are applied after checking the stationarity properties and long run cointegration among the variables. According to the empirical findings, natural resources have significant positive impact, whereas eco-innovations have negative impact on CO2 emission in Pakistan. Bi-directional causal association is present between CO2 and eco-innovations, and CO2 and economic growth, but no causal association is present between natural resources and CO2 emission. In addition, Variance Decomposition Analysis and Impulse Response Function show the forecasted effects of natural resources, eco-innovations and economic growth on future CO2 emissions. The findings are robust to various policy recommendations. The study recommends the policymakers and the government to implement strict regulations to curb the over utilization of natural resources. Government should also start new businesses and research and development programs in collaboration with private sector to promote eco-friendly technologies that will help in mitigation of environmental pollution in Pakistan.